Epithelial ovarian cancer mortality among Hispanic women: Sub-ethnic disparities and survival trend across time: An analysis of SEER 1992–2013. (February 2018) - Chen, Chen; Markossian, Talar W.; Silva, Abigail; Tarasenko, Yelena N.
Highlights: Ovarian cancer mortality in Hispanic patients varies by sub-ethnicity. Puerto Ricans have higher ovarian cancer death risk than other Hispanic subgroups. The 5 year ovarian cancer survival rate did not significantly change in 1992–2008. Combined analyses of all Hispanic patients may ignore subgroup mortality risks. Further research of Hispanic sub-ethnic disparities in ovarian cancer is warranted. Abstract: Background: Over the past half century the proportion of Hispanics in the US population has been steadily increasing, and groups of Hispanic origin have diversified. Despite notable racial and ethnic disparities in ovarian cancer (OC) mortality, population-based studies on OC among Hispanic females are lacking. Objectives: To examine sub-ethnic disparities in OC mortality and survival trends using the Surveillance, Epidemiology, and End Results Program (SEER) 18 data on Hispanic women diagnosed with epithelial OC during 1992–2013. Methods: The disparities in OC 5 year survival and mortality were examined using log-rank tests and Cox proportional hazards models, adjusted for sociodemographic and pathological characteristics, time of diagnosis, receipt of resection surgery and county socioeconomic status. Trends in 5-year survival rates were examined using joinpoint regression models. Results: The 5-year survival was lowest in Puerto Ricans (median survival: 33 months; survival rate: 31.07%) and was highest in the "Other" Hispanic subgroup (median survival: 59 months; survival rate: 49.14%) (log-rank test: P < 0.001). The OC-specific death hazards in Mexicans (HRadj : 0.82, 95%CI: 0.67–1.00, P = 0.048), South or Central Americans (HRadj : 0.77, 95%CI: 0.62–0.96, P = 0.005) and Other Hispanics (HRadj : 0.76, 95%CI: 0.63–0.92, P = 0.038) were significantly lower than for Puerto Ricans. Mortality rates of Cubans and Puerto Ricans were not significantly different. During 1992–2008, there were non-significant increasing trends in the 5-year all-cause and OC-specific survival rates: from 43.37% to 48.94% (APC = 0.41, P = 0.40) and from 48.72% to 53.46% (APC = 0.29, P = 0.50), respectively. Conclusions: OC mortality in Hispanic patients varied by sub-ethnicity. This heterogeneity should be considered in future cancer data collection, reports and research.